2022
DOI: 10.1001/jamapediatrics.2022.3172
|View full text |Cite|
|
Sign up to set email alerts
|

Nonpharmacological Interventions to Lengthen Sleep Duration in Healthy Children

Abstract: ImportanceAdequate sleep duration is necessary for many aspects of child health, development, and well-being, yet sleep durations for children are declining, and effective strategies to increase sleep in healthy children remain to be elucidated.ObjectiveTo determine whether nonpharmaceutical interventions to improve sleep duration in healthy children are effective and to identify the key components of these interventions.Data SourcesCENTRAL, MEDLINE, Embase, PsycINFO, Web of Science Core collection, ClinicalTr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 94 publications
1
12
0
Order By: Relevance
“…Furthermore, parental knowledge of child sleep seems to be associated with earlier child bedtimes and wake times and more consistency between weekend and weekday sleep routines [ 57 ]. A recent meta-analysis also showed that interventions aimed at an earlier child bedtime resulted in 47 min more of child sleep a night [ 58 ]. Therefore, spreading knowledge about the different adverse outcomes of child eveningness may motivate parents and professionals to find the appropriate means to steer a child’s diurnal rhythm toward one that favors well-being.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, parental knowledge of child sleep seems to be associated with earlier child bedtimes and wake times and more consistency between weekend and weekday sleep routines [ 57 ]. A recent meta-analysis also showed that interventions aimed at an earlier child bedtime resulted in 47 min more of child sleep a night [ 58 ]. Therefore, spreading knowledge about the different adverse outcomes of child eveningness may motivate parents and professionals to find the appropriate means to steer a child’s diurnal rhythm toward one that favors well-being.…”
Section: Discussionmentioning
confidence: 99%
“…Kishan M. Thadikonda, MD; Katherine M. Gast, MD, MS There are an estimated 1.6 million transgender people in the United States, of which 300 000 are younger than 18 years. 1 Transgender, nonbinary, and gender expansive/ nonconforming (TNG) patients experience health disparities including increased levels of poverty, homelessness, and suicidality. 2 Among transgender youth, one-half consider suicide and over a third attempt it.…”
Section: Role Of the Funder/sponsormentioning
confidence: 99%
“…Children’s sleep duration matters and it is in our power to change it. This is 1 of 2 cut-through findings of the systematic review and meta-analysis by Magee et al of interventions in this issue of JAMA Pediatrics , spanning 45 randomized clinical trials and nearly 14 000 children and adolescents aged 1 to 18 years. Specifically, sleep can be lengthened by around half an hour each night simply by encouraging earlier bedtimes.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…Prior research has shown that a 30 minute increase in sleep duration can lead to improvements in clinically relevant outcomes in children 7,8 . However, a meta-analysis reported that current sleep interventions for children increase average sleep duration by 10 minutes per night and most have been conducted in the school setting 9 .…”
Section: Introductionmentioning
confidence: 99%